Escalas temporais do escoamento noturno dentro e acima de um dossel na Amazônia - Santos, Daniel Michelon dos (2015)
This work uses data from the three components of wind and temperature, collected in an experimental site in the Amazon rainforest for 10 months during GOAmazon Project. A total of 10 levels of sensors were deployed on a micrometeorological tower. Focusing on the nocturnal boundary layer, an analysis of the temporal scales of the motion, using the multiresolution decomposition, has shown that the contributions from horizontal, nonturbulent fluctuations with long temporal scales, can be as significant as purely turbulent fluctuation. On, weakly stable nights the dominant temporal scales of the flow are those associated with, downward (sweeps) and upward events (ejections), which occur with fullydeveloped turbulence, , having dominant time scales between 10 and 100 s. Through the analysis of two-point correlations, it was possible to show that horizontal events with long time scales propagate from the top to within the canopy, being detected at different times, and. The vertical component correlations are larger at the upper canopy, not showing any time delay. The occurrence of positive sensible heat flux near the surface, with times scales larger than 100 s, has been identified in the study of overall averages. It is hypothesized that on very stable nights, non-turbulent modes associated with longer time scales, and referred as "submeso" have great impact on the horizontal components, becoming an important cause of the flow near the forest floor. In these situations, the most relevant time scales are longer than 300 a and dominate the almost entire vertical profile. For these cases, the correlations of turbulent variables decay rapidly a, being between 0.2 and 0.3 for the horizontal components while not exceeding 0.1 for the vertical component does. This reinforces the hypothesis that, for this scenario, the most correlated events between the top of the canopy and its interior are horizontal in nature.